If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(m + -23) = 27 + -3(m + -2) Reorder the terms: 3(-23 + m) = 27 + -3(m + -2) (-23 * 3 + m * 3) = 27 + -3(m + -2) (-69 + 3m) = 27 + -3(m + -2) Reorder the terms: -69 + 3m = 27 + -3(-2 + m) -69 + 3m = 27 + (-2 * -3 + m * -3) -69 + 3m = 27 + (6 + -3m) Combine like terms: 27 + 6 = 33 -69 + 3m = 33 + -3m Solving -69 + 3m = 33 + -3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3m' to each side of the equation. -69 + 3m + 3m = 33 + -3m + 3m Combine like terms: 3m + 3m = 6m -69 + 6m = 33 + -3m + 3m Combine like terms: -3m + 3m = 0 -69 + 6m = 33 + 0 -69 + 6m = 33 Add '69' to each side of the equation. -69 + 69 + 6m = 33 + 69 Combine like terms: -69 + 69 = 0 0 + 6m = 33 + 69 6m = 33 + 69 Combine like terms: 33 + 69 = 102 6m = 102 Divide each side by '6'. m = 17 Simplifying m = 17
| x+5=4x-4 | | 15=-2+n | | 615=15n+75 | | -8=p-10 | | 0=a-18 | | 38-13=5(x-1) | | 28x-7y=-7 | | 0.5*x+0.25*x=16 | | 5x+10=28-x | | n-20=-10 | | x+22+4x=-46-4x-49 | | 8x+5=6(x+6) | | 10a-3a= | | b-1=-4 | | 6x+39=14x-23 | | 21-r=7 | | 5(x-1)+2x=7(x-3)+4 | | x-12=-41 | | 24-6x=15+3x | | 4-5y=6(3-2y) | | 8=19+x | | 3(2x-3)+11=8 | | 3x+36=8-4x | | -6=k-11 | | 5x-3=6x+9 | | 3(6-0.0033333333y)+y=18 | | 3=3a+18 | | 11x-14=107 | | 11x=97 | | 3(x+9)+129=180 | | 4(3u+5)=8u+14 | | 8(a+b)+3z=-9 |